Lethal and Sublethal Effects of Annona spp. Derivatives on Bemisia tabaci MEAM 1 (Hemiptera: Aleyrodidae) in Tomato - Soares, Muriel Cicatti Emanoeli [UNESP]; Baldin, Edson Luiz Lopes [UNESP]; do Prado Ribeiro, Leandro; dos Santos, Maria Clézia [UNESP]; Batista, Yago [UNESP]; Vendramim, José Djair (Springer Nature, 2021)
The whitefly Bemisia tabaci(Gennadius) MEAM 1 is one of the main insect species that colonize tomato plants and cause direct and indirect damage. The use of botanical derivatives may be a valuable method of insect control to reduce the inappropriate use of synthetic insecticides on crops. In this study, we evaluated the bioactivity of ethanolic extracts prepared from Annonaceae species compared to that of the commercial insecticides based on acetogenins (Anosom® 1 EC, anonine 10,000 mg L−1) and thiamethoxam (Actara® 250 WG) on eggs, nymphs, and adults of the whitefly in tomato. Initially, the effects of the ethanolic seed extracts of Annona mucosa (Jacq.), Annona muricata L., and Annona sylvatica A.St.-Hil on adult insect behavior were evaluated. The rates of infestation and oviposition deterrence indicated the inhibitory effects of the extract of A. muricata (500 mg L−1). Then, the possible systemic effects of the extracts were evaluated; however, no effects on nymphal development or insect viability were observed. The LC50 and LC90 of the ethanolic extract of A. mucosa seeds at 500 mg L−1 (10.83 and 200.24 mg L−1, respectively) were estimated and were used in ovicidal tests and compared to positive (Actara® 250 WG and Anosom® 1 EC), and negative controls (water: acetone, 1:1 v/v). At LC90, fewer eggs (35.00%) had hatched at 13 days after application than in the other treatments. The results of this study demonstrate the potential use of botanical derivatives of Annona spp. for the management of B. tabaci MEAM 1 in tomato.
Keywords: acetogenins; deterrence; mortality; repellence; Silverleaf whitefly